Development of an antisense oligonucleotides-based therapy for mucolipidosis type II α/β: in vivo studies - Gonçalves, Mariana (2022)
Introduction: The RNA molecule has become an increasingly promising target for the therapy of various diseases. Mucolipidosis type II α/β (ML II α/β) is one of the most severe Lysosomal Storage Disorders and is caused by the deficiency of the enzyme GlcNAc-1- phosphotransferase. This enzyme is responsible for the addition of the mannose 6-phosphate (M6P) marker to lysosomal enzymes, which allow their targeting to lysosomes. GlcNAc-1- phosphotransferase is encoded by the GNPTAB and GNPTG genes. Of the several mutations that occur in ML II α/β, the deletion of 2 nucleotides from GNPTAB exon19 (c.3503_3504del) is the most frequent, being a good target for a mutation specific therapy as there is no therapy for this disease 1,2. In this study, we explored the possibility of an innovative therapeutic strategy based on the use of antisense oligonucleotides (AOs) for ML II. In a previous in vitro study in ML II patient fibroblasts, AOs were used to promote the exon 19 skipping from the GNPTAB pre-mRNA, resulting successfully in the production of an in-frame mRNA 3. Currently, our objective is to evaluate the therapeutic potential of this approach in vivo in mice (Mus musculus) of the strain C57BL/6. Material & Methods: Eighteen animals with an average body mass of 25 g were used. During the study, individual body weight, food and water intake were recorded. The animals were divided into 6 groups: groups 1 and 4 were injected with saline solution, groups 2 and 5 were injected with AO at 25 mg / kg and groups 3 and 6 were injected with AO at 50 mg / kg. All animals were injected intraperitoneally and sacrificed after 4 days (groups 1, 2 and 3) or after 7 days (groups 4, 5 and 6). At the end of the experiment, the organs were collected, weighted and frozen at -80ºC, for later RNA extraction, cDNA synthesis and PCR. Statistical analysis was performed using the GraphPad Prism® for Windows program. Statistical significance between groups was determined by analysis of variance (ANOVA), followed by a Bonferroni test. All ethical issues were followed by the guidelines of the Portuguese General Directorate of Food and Veterinary. Results: Our results show that mice from groups 5 and 6 have a lower liver mass compared to the other groups, with significant differences (p <0.05). Liver of animals from group 3 has a lower weight compared to the liver of animals from group 2 and group 4, with a statistically significant difference. However, exon 19 skipping was not observed in any organ sample using any of the tested doses or incubation periods. Conclusions: To explain these first in vivo results we can theorize that the doses administered were not sufficient to achieve a response or the AO may have had a high clearance rate or did not recognize the target RNA. Moreover, the collected organs should have been preserved in liquid nitrogen to maintain RNA integrity. Other experiments will be done in the near future to overcome these preliminary data. References: [1] R. V. Velho et al. Human mutation. [2] M. F. Coutinho, et al. Biochemistry research international [3] L. Matos, et al. Human Gene Therapy.